Exogenous salicylic acid alleviates cold damage by regulating antioxidative system in two barley (Hordeum vulgare L.) cultivars. Issue 2 (2nd April 2016) - Mutlu, Salih; Atıcı, Ökkeş; Nalbantoğlu, Barbaros; Mete, Ebru
ABSTRACT: In this work, the time-dependent effect of exogenous salicylic acid (SA) applied before cold stress was investigated on the regulation of antioxidative respond mechanisms in two barley ( Hordeum vulgare L.) cultivars (Akhisar and Tokak) differed in cold tolerance. SA (0.1 mM) was applied to 7-days old barley seedlings growing under control conditions (20/18°C). After this application, the seedlings were transferred to cold conditions (7/5°C) at different times (7, 14, 21 and 28 days) for 3 days. Then, the contents of malondialdehyde (MDA), hydrogen peroxide (H2 O2 ) and the activities of antioxidant enzymes such as superoxide dismutase (SOD), catalase (CAT) and peroxidase (POX) were determined in the leaves (control, cold and SA + cold) from the seedlings harvested at 10, 17, 24 and 31 days. Moreover, the effect of cold stress was evaluated on the endogenous SA level at the both cultivars by comparing to control plants. The MDA content increased in the cold treatment while it decreased in the SA treatment at all the days studied at the both cultivars. The SA + cold treatment could have a variable effect on H2 O2 content at the tolerant barley (Tokak) while decreased its content at the sensitive cultivar (Akhisar). The SA + cold treatment could increase the activities of POX and SOD at both cultivars, but it increased the CAT activity at the tolerant cultivar while decreased at the sensitive cultivar. In addition, the content of endogenous SA was decreased by cold stress at all the days studied at the barley cultivars as compared to control plants. The results show that the SA treatment could be effective on the regulation of the parameters studied at cold conditions until 31 days after SA application, and the importance of exogenous SA treatment before cold stress. It was concluded that exogenous and endogenous SA could play an ameliorating role on cold tolerance by regulating reactive oxygen species and the activities of antioxidative enzymes in both cold-sensitive and cold-tolerant cultivars of barley.